Impact of the National Amyotrophic Lateral Sclerosis Registry: Analysis of Registry‐funded Research. Issue 11 (19th October 2022) - Rechtman, Lindsay; Brenner, Stephan; Wright, Marcienne; Ritsick, Maggie; Rahman, Farhana; Han, Moon; Raymond, Jaime; Larson, Theodore; Horton, D. Kevin; Mehta, Paul
Abstract: Objective: This research aims to examine the impact of the National Amyotrophic Lateral Sclerosis (ALS) Registry‐funded research activities. Methods: Registry‐funded research and related publications were identified through the National ALS Registry website, the National Institutes of Health (NIH) Reporter website, and verified by Principal Investigators. Key study characteristics (e.g., study population, sample size) and key impact features (e.g., risk factors) were abstracted and recorded on study abstraction forms. Descriptive statistics were used to analyze the volume, productivity, and findings of the Registry‐funded research. Results: Since 2012, the National ALS Registry funded 21 research projects. Of these, 14 were through extramural research grants and included in the analysis. These studies are often related to environmental, medical conditions, and genetic risk factors. On average, the funded grants produced 1 to 2 publications which were cited 114 times by other researchers. The relative citation ratio averaged 1.81 with a weighted relative citation ratio of 16.28. These studies supported the identification and confirmation of candidate risk factors. Environmental and occupational risk factors typically related to heavy metal exposure (e.g., lead, mercury) and agricultural chemicals (e.g., pesticides, herbicides), and the occupations associated with exposure to these substances were most frequently explored. Interpretation: The National ALS Registry is a multifaceted research platform, one component of which is funded research. This Registry‐funded research fills an essential gap in the overall ALS scientific community as it is difficult to prevent and treat a disease without a deeper understanding of its causes.